Description Of 10 Example Of Export Import Commodities Development Against Foreign Exchange Reserves On Indonesia Trade Balance (Period 2018-2022) - Longdong, Reynaldi Esau; Halim, Prihartono Aksan (Publikasi Indonesia, 2023)
This study aims to provide a detailed overview of Indonesia's trade balance on the export-import commodities. This research used data obtained from various sources, including the Indonesian Ministry of Trade for 5 years from 2018 to 2022. This research used secondary data and the method used to explain this research is a descriptive approach. This research provides an overview of Indonesia's trade patterns in 2018-2022, analyzing trends of exports and imports commodities. In addition, this study also examines the impact of various factors, such as trade policy on Indonesia's trade balance. The results of the study explain that the export trade balance is higher than the imports where the export trend value in 2018-2022 is 15% compared to the Import trend value of 6%. It can be concluded that Indonesia's export and import commodities trade balance in 2018-2022 can be called a surplus because the export value from 2018-2022 is greater than the import value.